Critical analysis of methods for measuring and monitoring of the population life quality - A. A. Golovin (Управление)
One of the problems of public administration is the need to select the best criteria for assessing the quality of life of the population. The aim of the study is to provide a critical analysis of current approaches to measuring and monitoring the quality of life of the population. The object of the study is the quality of life of the population. The subject of the research is approaches to measuring and monitoring the quality of life of the population.The article provides a comparative characteristic of the prevailing classes of measures used in economics. The advantages and disadvantages of natural, monetary, physical, power, temporal, dimensionless units of quality of life have been analysed. The main foreign and domestic approaches to such monitoring have been considered and the positions of the Russian Federation in foreign ratings of the quality of life have been indicated. Using the methods of content analysis, comparison, systems analysis, expert assessment, etc., the features of contemporary quality of life assessment tools have been highlighted. Global, subnational and national quality of life assessment methods in relation to measurement tools have been compared and a comparative analysis has been presented in a summary graph.The author’s classification of quality of life management approaches has been presented. Historical and economic analysis allows us to distinguish between the monetarist approach, the social justice approach, and the physico-economic approach. Monetary methods of managing the quality of life of the population are based on financial and economic factors and monetary measurement tools, the social justice approach is based on the study of socio-psychological factors and life satisfaction indicators, the physical and economic approach reconciles the needs of the socio-economic system with the capabilities of the natural environment and uses power units of measurement. Foreign research in recent years has been dominated by subjective (socio-psychological) measurement methods, whereas in Russian research objective measurement indicators still play a major role in monitoring quality of life.The article offers recommendations for developing an improved methodology for assessing the quality of life of the population using social time.